Training in Improving the Citizen's Economy During the Covid-19 Pandemic (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Micro, small and medium-sized enterprises (MSMEs) are an important part of the economy of a country or region. This important role has encouraged many countries, including Indonesia, to continue to strive to develop MSMEs. Even though it is small the number of workers, assets, and turnover, because the number is quite large, the role of MSMEs is quite important in supporting the economy. Lembang, which is located in the west bandung district area, is one of the favorites and leading tourist attractions in West Java. Presenting various natural beauties supported by cool mountain air. Apart from Lembang, actually, in the West Bandung district area, there are still many tourism potentials that can be developed. One of them is in the Parongpong area which is next to Lembang. There are seven villages in Parongpong District that have this potential, such as Cihideung Village which is already known as an area of ​​ornamental plants. Other villages, Cigugur Girang, Cihanjuang Rahayu, Cihanjuang, Sariwangi, Ciwaruga, Karyawangi, also have different tourism potential and uniqueness, including improving the community's economy and Village-Owned Enterprises (Bumdes) to “skyrocket” at the national or international level.